“Fistula Zero” Project After Total Laryngectomy: The Candiolo Cancer Institute Experience - Crosetti, Erika; Arrigoni, Giulia; Sprio, Andrea Elio; Succo, Giovanni (Frontiers in Oncology, 2021)
Objectives Pharyngocutaneous fistula (PCF) is a troublesome complication after total laryngectomy. The “Fistula zero” project aims to reduce the number of PCF by following a detailed protocol based on three fundamental key points. Materials and Methods The Fistula zero project included 77 patients who underwent total laryngectomy in the period from January 2019 to December 2020. The protocol consisted of three main aspects: the systematic placement of a Har-El salivary bypass tube, the continuous horizontal watertight pharyngeal suture using a barbed suture, onlay insetting of a pedicled flap in pre-treated patients. Results One case of PCF (1.3%) and three small blind fistulas (3.9%) were observed in this series. The mean length of hospitalization was 18 days. Conclusion Pharyngocutaneous fistula (PCF) prolongs hospitalization and delays adjuvant treatments. Thanks to a strict adherence to the protocol, it was possible to reduce PCF rates, avoiding lengthy hospitalization and additional surgical procedures.